Dynamics of the rice rhizosphere microbial community under continuous and intermittent flooding treatment. (1st November 2019) - Li, HaiLong; Yu, Yong; Guo, JingXia; Li, Xiangzhen; Rensing, Christopher; Wang, Guo
Abstract: Flooding regime is an important agronomic strategy, and widely applied in heavy metal-contaminated soil for controlling heavy metal uptake through biochemical processes. However, the dynamics of the microbial community in the rhizosphere of rice under different flooding systems are not well understood. In the present study, we investigated the dynamics between the microbial community and heavy metal ions under continuous flooding (CF) and intermittent flooding (IF) conditions to decipher the relationship between microbial community and environmental factors. The results showed that, for the complex Cd, Pb, and Zn contaminated soil under CF treatment did not significantly suppress Cd uptake, but promoted Pb and Ni accumulation into the rice root. Soil pH and bio-available phosphate content appeared to be the key factors impacting heavy metal mobility. When observing the microbial community in the rhizosphere, long term flooding resulted in an abundance of Anaeromyxobacter sp., Geobacter and Desulfovibrio, and the abundance of these taxa displayed a significant relationship to Pb and Zn content of rice roots. From the study, we observed that the flooding regime could have a significant impact on concentrations of Cd, Pb and Ni in rice roots, and the different richness of SRB and FeRB may contribute to uptake of these heavy metals. In future work, the impact of Fe cycling on heavy metal bioavailability in the plant rhizosphere should be investigated further. Highlights: Compared rhizobacterial composition and diversity under two flooding regimes. Observed dynamic changes in bacterial community from rice tillering to ripening. Long-term flooding could enhance Fe and S reducing bacteria in the rhizosphere. Shown relationship between certain bacteria and root heavy metal content.